The Economic Determinants of Systematic Risk - Robichek, Alexander A.; Cohn, Richard A. (Journal of Finance, 1974)
Alexander A. Robichek, Richard A. Cohn, The Economic Determinants of Systematic Risk, The Journal of Finance, Vol. 29, No. 2, Papers and Proceedings of the Thirty-Second Annual Meeting of the American Finance Association, New York, New York, December 28-30, 1973 (May, 1974), pp. 439-447